2021
DOI: 10.11591/ijai.v10.i1.pp93-100
|View full text |Cite
|
Sign up to set email alerts
|

Expert role in image classification using CNN for hard to identify object: distinguishing batik and its imitation

Abstract: <span id="docs-internal-guid-25a2977b-7fff-96bd-b93a-19bd55e68ea7"><span>In this research we try to solve the recognition problem in differentiating between batik and its imitation. Batik is an Indonesian heritage of process in making traditional textile product that is now endangered by the existence of imitation products. We try to compare two popular CNN model to classify batik products into five classes. The classes are tulis, cap, print warna, print malam, cabut warna. Tulis and cap are genuin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Nevertheless, a computer-aided design was not employed in this work to avoid overloading them with too many new things at once. Computer programs were previously proven successful in batik designs [17][18][19][20], but the local batik artisans were not keen to use them. The gradual incorporation of new techniques into traditional craftsmanship is an appropriate way to transform batik into modern fashion without losing its local identity and charm.…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a computer-aided design was not employed in this work to avoid overloading them with too many new things at once. Computer programs were previously proven successful in batik designs [17][18][19][20], but the local batik artisans were not keen to use them. The gradual incorporation of new techniques into traditional craftsmanship is an appropriate way to transform batik into modern fashion without losing its local identity and charm.…”
Section: -Discussionmentioning
confidence: 99%
“…Laitupa et al demonstrated the computer-based creation of new batik motifs [17], whereas Tian et al developed automatic batik flower patterns based on fractal geometry [18]. For pattern recognition, neural networks and deep learning have been implemented on batik fabrics [19,20]. To characterize fabric colors, smartphone colorimetry was demonstrated and compared with the standard CIE L*a*b* color measurement using a HunterLab spectrophotometer [21].…”
mentioning
confidence: 99%
“…The structure of MobileNetV2 can be seen in Fig 3 . MobileNetV2 has been tested on ImageNet classification. In addition, MobileNetV2 was also tested on pattern recognition of traditional clothes [24] and batik image classification [25]. The MobileNetV2 model uses a convolution block with a unique property that separates the model network's expressiveness capacity by using an input bottleneck [26].…”
Section: Modelsmentioning
confidence: 99%
“…The MobileNetV2 model uses a convolution block with a unique property that separates the model network's expressiveness capacity by using an input bottleneck [26]. 2) InceptionV3 and InceptionResNetV2: InceptionV3 was introduced by Widyantoko et al [25]. InceptionV3 enhances the model network by making the most efficient use of incremental computing with suitable factored convolution and aggressive regularization.…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation